2022
DOI: 10.1155/2022/6878783
|View full text |Cite|
|
Sign up to set email alerts
|

Multimodal Medical Image Fusion of Positron Emission Tomography and Magnetic Resonance Imaging Using Generative Adversarial Networks

Abstract: Multimodal medical image fusion is a current technique applied in the applications related to medical field to combine images from the same modality or different modalities to improve the visual content of the image to perform further operations like image segmentation. Biomedical research and medical image analysis highly demand medical image fusion to perform higher level of medical analysis. Multimodal medical fusion assists medical practitioners to visualize the internal organs and tissues. Multimodal medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In synchrotron tomography, conventional and machine learning methods 120 , 121 are still considered the most popular, while DL approaches from other data-intensive scientific fields are also worth investigating. GAN-based architectures have been found to be effective 122 , 123 in performing registration and correlation from different modalities because the end-to-end generative nature of multimodal tomographic data fusion workload is well suited. In 2022, Abirami et al.…”
Section: Scientific Application-oriented Data Processing On Reconstru...mentioning
confidence: 99%
See 1 more Smart Citation
“…In synchrotron tomography, conventional and machine learning methods 120 , 121 are still considered the most popular, while DL approaches from other data-intensive scientific fields are also worth investigating. GAN-based architectures have been found to be effective 122 , 123 in performing registration and correlation from different modalities because the end-to-end generative nature of multimodal tomographic data fusion workload is well suited. In 2022, Abirami et al.…”
Section: Scientific Application-oriented Data Processing On Reconstru...mentioning
confidence: 99%
“…In 2022, Abirami et al. 122 used GAN to successfully register single-layer slices obtained from magnetic resonance imaging (MRI) and positron emission tomography (PET) scans, achieving excellent contrast on soft tissues using MRI and better spatial characteristics on bones using PET. The advantages of the two modalities are effectively complemented through modality fusion.…”
Section: Scientific Application-oriented Data Processing On Reconstru...mentioning
confidence: 99%
“…To combine these intensities of four modalities and provide more informative MRI brain tumor image, image fusion is introduced in this process. The method of combining different images that will produce single image with good quality is referred as image fusion [3].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%